2015
DOI: 10.1038/srep11204
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance of cardiac gene expression and cardiomyocyte structure predisposes Mecp2-null mice to arrhythmias

Abstract: Methyl-CpG-binding protein 2 (MeCP2) is an epigenetic regulator of gene expression that is essential for normal brain development. Mutations in MeCP2 lead to disrupted neuronal function and can cause Rett syndrome (RTT), a neurodevelopmental disorder. Previous studies reported cardiac dysfunction, including arrhythmias in both RTT patients and animal models of RTT. In addition, recent studies indicate that MeCP2 may be involved in cardiac development and dysfunction, but its role in the developing and adult he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…In our laboratory, Mecp2 -null mice exhibited reduced spontaneous movement between 3 and 8 weeks of age, and died at approximately 7–10 weeks 25 . At the late stages of disease (7–10 weeks), most Mecp2 -null mice exhibited reduced mobility and severe weakness.…”
Section: Resultsmentioning
confidence: 99%
“…In our laboratory, Mecp2 -null mice exhibited reduced spontaneous movement between 3 and 8 weeks of age, and died at approximately 7–10 weeks 25 . At the late stages of disease (7–10 weeks), most Mecp2 -null mice exhibited reduced mobility and severe weakness.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, there is evidence for symptoms affecting peripheral tissues, and the efforts to understand the impact of MECP2 mutations in the function of other systems in the organism have recently led to more detailed descriptions of phenotypes affecting the respiratory, cardiovascular, and immune systems [4, 6, 13, 14]. Symptoms affecting the gastrointestinal tract of RTT patients are common, but how the absence of MECP2 impacts intestinal function is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies used a combination of four distinct neuronal cell populations including thick tufted pyramidal neurons from the motor cortex, fast‐spiking parvalbumin‐positive interneurons from the motor cortex, noradrenergic locus coeruleus neurons, and cerebellar Purkinje cells (Ehrhart et al, ; Sugino et al, ). Other studies used astrocytes (Delepine et al, ; Yasui et al, ) and microglia and peritoneal macrophages (Cronk et al, ), while others used cardiovascular progenitor cells (Hara et al, ) and cortical callosal projection neurons (Kishi et al, ). Studies using cell sources not originating from brain regions include the use of fibroblasts (Orlic‐Milacic et al, ), skeletal muscle (Gold et al, ), and blood (Sanfeliu et al, ).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Although MECP2 is expressed in a wide range of tissues, Rett syndrome is principally caused by the deficiency of MeCP2 in the cells of the brain (Chen, Akbarian, Tudor, & Jaenisch, ) and thus apart from four studies (Gold et al, ; Hara et al, ; Orlic‐Milacic et al, ; Sanfeliu et al, ), all transcriptional murine studies were confined to the brain. A handful of studies focused on the transcriptome of the whole brain (Guo et al, ; Kriaucionis et al, ; Nuber et al, ) however these studies revealed only subtle changes in gene expression which can be attributed to the brain being a heterogeneous organ consisting of many distinct functional regions that may individually be affected by the lack of Mecp2.…”
Section: Dysregulated Biological Network and Cellular Functionsmentioning
confidence: 99%